HLA‐G regulatory polymorphisms are associated with susceptibility to HCV infection. (13th January 2017) - Catamo, E.; Zupin, L.; Freato, N.; Polesello, V.; Celsi, F.; Crocè, S. L.; Masutti, F.; Pozzato, G.; Segat, L.; Crovella, S.
Abstract : Background: Hepatitis C virus (HCV) is able to bypass the immune system modulating innate and adaptive immune response and blocking T helper 1 (Th1) cell production. Because the human leukocyte antigen (HLA)‐G molecule has immunomodulatory properties inhibiting the function and production of natural killer and cytotoxic lymphocyte T cells, as well as promoting shift from Th1 toward Th2 response, we hypothesized its involvement in susceptibility to HCV infection. Materials and Methods: Considering that HLA‐G mRNA expression has been reported to be under genetic control, an association study was conducted analyzing 800 base pairs upstream the ATG at the 5′upstream regulator region (URR) and 850 base pairs from ATG to exon 3 and the 3′untranslated region (UTR) of HLA‐G gene in Italian HCV‐positive patients and uninfected controls. Results: Four 5′URR polymorphisms (−725C>G>T, −509C>G, −400G>A and −398G>A), 7 polymorphisms at coding region (+15G>A, +36G>A, +243G>A, insC506, 531G>C, delA615 and 685G>A), the +644G>T polymorphism, and 1 haplotype (TTGTTCCIGAC) showed different frequency distributions between HCV patients and uninfected controls. Conclusion: The results from our study suggest a possible involvement of HLA‐G in the risk modulation toward HCV infection.